2007
DOI: 10.1007/s11430-007-6003-4
|View full text |Cite
|
Sign up to set email alerts
|

Zircon SHRIMP U-Pb ages and trace element geochemistry of the Kuhai gabbro and the Dur’ngoi diorite in the southern east Kunlun tectonic belt, Qinghai, Western China and their geological implications

Abstract: Timing of the intermediate-basic igneous rocks developed in the area of Kuhai-A'nyêmaqên along the southern east Kunlun tectonic belt is a controversial issue. This paper presents new zircon SHRIMPU-Pb dating data for igneous zircons from the Kuhai gabbro and the Dur'ngoi diorite in the Kuhai-A'nyemaqen tectonic belt, which are 555±9 Ma and 493±6 Ma, respectively. The trace element geochemical features of the Kuhai gabbro and the Dur'ngoi diorite are similar to those of ocean island basalts (OIB) and island ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This age is significantly later than that of the Buqingshan tectonic mélange Delisitan oceanic ridge ophiolite (gabbros aged 516.4 ± 6.3 to 467.2 ± 0.9 Ma; Bian et al ., ; Liu et al ., ), Majixueshan oceanic ridge ophiolite in the A'nyemaqen Tectonic Mélange Belt (535 ± 10 Ma) (Li et al ., ), Qingshuiquan ophiolite in the central eastern Kunlun Tectonic Mélange Belt (522.3 ± 4.1 to 507.7 ± 8.3 Ma) (Yang et al ., ; Lu et al ., ; Li et al ., ; Chen et al ., ; Ren et al ., ), and ancient ocean basin remnants of the Kekesha–Kekekete mafic–ultramafic mélange (509.4 ± 6.8 to 501 ± 7 Ma) (Feng et al ., ; Li et al ., ). This age is earlier than that of the Yikehalaer island‐arc granodiorite rock mass (437.5 ± 6.6 Ma to 402 ± 24 Ma; Bian et al ., ; Liu, ; Li et al ., ), the Bairiqiete island‐arc granodiorite (441.1 ± 6.3 Ma to 439.0 ± 1.9 Ma; Liu et al ., ; Li et al ., ), and acidic volcanic lava (437.7 ± 2.8 Ma; Liu et al ., ) in the Buqingshan–A'nyemaqen Early Palaeozoic Tectonic Mélange Belt, and similar to the Dur'ngoi island‐arc diorite age (493 ± 6 Ma; Li et al ., ). Finally, the post‐collision granitoids of the East Kunlun Orogen (411 ± 17 Ma to 394 ± 13 Ma; Liu et al , ; Zhao et al , ; Chen et al , ; Long et al , ), Helegangnaren A‐type granites of the north side of the East Kunlun Fault (425 ± 7 Ma, Li et al ., ), and the extension‐type molasse of the Maoniushan Formation in the north of East Kunlun Orogen and the northern margin of the Qaidam Basin (423.2 ± 1.8 Ma to 399.6 ± 2.8 Ma; Xu et al ., ; Li et al ., ; Lu et al ., ; Zhang et al , ) are significantly later than the Manite granodiorite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This age is significantly later than that of the Buqingshan tectonic mélange Delisitan oceanic ridge ophiolite (gabbros aged 516.4 ± 6.3 to 467.2 ± 0.9 Ma; Bian et al ., ; Liu et al ., ), Majixueshan oceanic ridge ophiolite in the A'nyemaqen Tectonic Mélange Belt (535 ± 10 Ma) (Li et al ., ), Qingshuiquan ophiolite in the central eastern Kunlun Tectonic Mélange Belt (522.3 ± 4.1 to 507.7 ± 8.3 Ma) (Yang et al ., ; Lu et al ., ; Li et al ., ; Chen et al ., ; Ren et al ., ), and ancient ocean basin remnants of the Kekesha–Kekekete mafic–ultramafic mélange (509.4 ± 6.8 to 501 ± 7 Ma) (Feng et al ., ; Li et al ., ). This age is earlier than that of the Yikehalaer island‐arc granodiorite rock mass (437.5 ± 6.6 Ma to 402 ± 24 Ma; Bian et al ., ; Liu, ; Li et al ., ), the Bairiqiete island‐arc granodiorite (441.1 ± 6.3 Ma to 439.0 ± 1.9 Ma; Liu et al ., ; Li et al ., ), and acidic volcanic lava (437.7 ± 2.8 Ma; Liu et al ., ) in the Buqingshan–A'nyemaqen Early Palaeozoic Tectonic Mélange Belt, and similar to the Dur'ngoi island‐arc diorite age (493 ± 6 Ma; Li et al ., ). Finally, the post‐collision granitoids of the East Kunlun Orogen (411 ± 17 Ma to 394 ± 13 Ma; Liu et al , ; Zhao et al , ; Chen et al , ; Long et al , ), Helegangnaren A‐type granites of the north side of the East Kunlun Fault (425 ± 7 Ma, Li et al ., ), and the extension‐type molasse of the Maoniushan Formation in the north of East Kunlun Orogen and the northern margin of the Qaidam Basin (423.2 ± 1.8 Ma to 399.6 ± 2.8 Ma; Xu et al ., ; Li et al ., ; Lu et al ., ; Zhang et al , ) are significantly later than the Manite granodiorite.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches of the Early Palaeozoic magmatic rocks have shown that there are old island‐arc magmatic characteristics in the Buqingshan–A'nyemaqen Tectonic Mélange Belt (Bian et al ., , b; Liu, ; Liu et al ., , b). The ages of these magmatic rocks are divided into two phases: the early phase is the Cambrian–Furongian (such as De Dur'ngoi diorite; Li et al ., ), and the later phase is Early Silurian (such as Yikehalaer granodiorite, Bairiqiete granodiorite, and acidic volcanic lava; Bian et al ., ; Liu, ; Li et al ., , respectively). The formation ages of this Early Palaeozoic magmatic are similar to the subduction time of the Proto‐Tethyan Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The East Kunlun Orogenic belt (E‐KOB) located in the northern Tibetan Plateau and the western part of the Central China Orogenic Belt has witnessed the subduction–accretion process of the Proto‐ and Palaeo‐Tethys Ocean, and accordingly was suggested as an accretionary orogen (Figure 1a,b; Dong et al, 2021; Dong, He, et al, 2018; Li et al, 2016; Song et al, 2018). During the long‐term subduction–accretion process, a series of Tethys oceanic crust fragments—ophiolitic mélanges (Bian et al, 2001, 2002, 2004; Li et al, 2007; Liu, Pei, Li, Li, Chen, Gao, et al, 2011; Liu, Pei, Li, Li, Zhang, et al, 2011; Yang et al, 2009), as well as related magmatic rocks (Bian et al, 2007; Li et al, 2017; Li, Pei, Li, Pei, Liu, et al, 2014; Wei, Gan, Bao, et al, 2018; Wei, Gan, Cang, & Kang, 2018; Xiong et al, 2015) are well preserved in the southern margin of the E‐KOB (Figure 1b). The Muztagh‐Buqingshan‐Anemaqen ophiolitic mélange zone (MBAM) is situated in the southern margin of the East Kunlun Orogenic Belt and is characterized by widely distributed ophiolitic mélange and different types of intrusive rock in the Muztagh, Buqingshan, and Anemaqen areas with formation ages of ca.…”
Section: Introductionmentioning
confidence: 99%
“…AKM, Aqikekulehu–Kunzhong ophiolitic mélange zone; MBAM, Muztagh–Buqingshan–Animaqen ophiolitic mélange zone (modified after Dong, He, et al, 2018); QXM, Qimantagh‐Xiangride mélange zone. Age data are from (1) Wei, Gan, Bao, et al (2018); (2) Wei, Gan, Cang, and Kang (2018); (3) Li et al (2017); (4) Bian, Pospelov, Li, Chang, and Li (2007); (5) Li, Pei, Li, Pei, et al (2015); (6) Liu, Pei, Li, Li, Zhang, et al (2011); (7) Liu, Pei, Li, Li, Chen, Chen, et al (2011); (8) Bian et al (2004); (9) Wang (2015); (10) Li (2008); (11) Xiong, Ma, Wu, Jiang, and Liu (2015); (12) Li, Li, Guo, Sun, and Zhang (2007); (13) Yang, Shi, Wu, Wang, and Robinson (2009); (14) Liu et al (2013). (c) Simplified geological map showing sample location in Marzheng area…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation